The Relationship Between Self-efficacy and Homesickness in New Students in the Islamic Boarding School Environment - Warisatul Fajrin; Maya Yasmin (Universitas Muhammadiyah Banjarmasin, 2023)
This study aims to determine the relationship between self-efficacy and homesickness in new students at Islamic boarding schools. This research is quantitative research with correlation data analysis of Product Moment. This research involved 322 new Islamic boarding school students in Agam Regency, West Sumatra using cluster random sampling technique. The scales used in this study are the General Self-efficacy Scale (GSES) belonging to Schwarzer (1995) and the homesickness scale which was self-compiled based on the theory of Stroebe et al. (2002). The results showed that there is a negative relationship between self-efficacy and homesickness in new students at Islamic boarding schools. So, to reduce homesickness in new students at Islamic boarding school, it is necessary to have a role of self-efficacy in new students.